Transcriptome and Metabolome Analyses Reveal Potential Salt Tolerance Mechanisms Contributing to Maintenance of Water Balance by the Halophytic Grass Puccinellia nuttalliana - Vaziriyeganeh, Maryamsadat; Khan, Shanjida; Zwiazek, Janusz J. (Frontiers in Plant Science, 2021)
Elevated soil salinity exacerbated by human activities and global climate change poses serious threats to plant survival. Although halophytes provide many important clues concerning salt tolerance in plants, some unanswered questions remain to be addressed, including the processes of water and solute transport regulation. We performed high-throughput RNA-sequencing in roots and metabolome characterizations in roots and leaves of Puccinellia nuttalliana halophytic grass subjected to 0 (control) and 150 mM NaCl. In RNAseq, a total of 31 Gb clean bases generated were de novo assembled into 941,894 transcripts. The PIP2;2 and HKT1;5 transcript levels increased in response to the NaCl treatment implying their roles in water and ion homeostasis. Several transcription factors, including WARKY39, DEK3, HY5, and ABF2, were also overexpressed in response to NaCl. The metabolomic analysis revealed that proline and dopamine significantly increased due to the upregulation of the pathway genes under salt stress, likely contributing to salt tolerance mechanisms. Several phosphatidylcholines significantly increased in roots suggesting that the alterations of membrane lipid composition may be an important strategy in P. nuttalliana for maintaining cellular homeostasis and membrane integrity under salt stress. In leaves, the TCA cycle was enriched suggesting enhanced energy metabolism to cope with salt stress. Other features contributing to the ability of P. nuttalliana to survive under high salinity conditions include salt secretion by the salt glands and enhanced cell wall lignification of the root cells. While most of the reported transcriptomic, metabolomics, and structural alterations may have consequences to water balance maintenance by plants under salinity stress, the key processes that need to further addressed include the role of the changes in the aquaporin gene expression profiles in the earlier reported enhancement of the aquaporin-mediated root water transport.